Performance of Different Genotypes of Gossypium hirsutum under Various Sowing Conditions on Yield Contributing Parameters - Raheel, Muhammad; Zaynab, Madiha; Anwar, Muhammad; Hussain, Ansar; Kanwal, Sonia; Bahuder, Khalida; Alvi, Anwaar; Ashraf, Muhammad Furqan; Iqbal, Zafar; Nadeem, Muhammad (PSM Biological Research, 2017)
This study was aimed to evaluate the performance of different cotton genotypes at Chishtian District, Bahawalnagar region. Four cotton genotypes (IUB-2013, FH-142, FH-LALAZAR and MNH-886) were sown under two different sowing times i.e., normal sowing S1 (20th April) and late sowing S2 (20th May 2016). The experiment design was split plot design with three replications in which genotypes were kept in main plot and sowing dates were in sub plot. Different agronomic practices were applied timely to insure healthy crop stand. Total yield and yield contributing parameters like number of bolls plant-1, boll weight (g), and seed cotton yield (kg/ha) were recorded. Genotype FH-142 showed best result for the trait number of bolls per plant (81.67) followed by genotype FH- Lalazar (80) under normal sowing condition. For number of bolls per plant under late sowing condition, FH-Lalazar depicted highest value (59.33) followed by FH-142 (55.67). For bolls per plant, FH-Lalazar depicted highest value (23.33 g) followed by FH-142 (22.67 g) and IUB-2013 (18.67 g) under normal sowing conditions. While under late sowing condition, FH-Lalazar dominated among all genotypes and displayed high value of boll weight (19.67 g). Genotype FH- LALAZAR showed highest seed cotton (5496 kg/ha) followed by FH-142 (5424.3 kg/ha) under normal sowing (S1). However, in case of late sowing (S2), FH-LALAZAR exhibited greater value of seed cotton yield followed by FH-142. The data regarding varying genetic diversity of the genotypes can be helpful to take measures for improving cotton yield per hectare.